The adoption of industry 4.0 practices by the logistics industry: A systematic review of the gulf region - Noorul Shaiful Fitri Abdul Rahman; Abdelsalam Adam Hamid; Taih-Cherng Lirn; Khalid Al Kalbani; Bekir Sahin (Cleaner Logistics and Supply Chain)
Industry 4.0 is a global approach that involves digitising some of the manufacturing, retailing, warehousing, transportation, and industrial procedures of the logistics industry. This present review aims to systematically review the adoption of Industry 4.0 technologies in the Gulf Cooperation Council (GCC) region, with a focus on the logistics industry. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) method were used to conduct a systematic review and comparative study of the GCC countries. The results indicate that the adoption of Industry 4.0 technologies by the logistics industries of the GCC countries is still at the nascent stage. This present review provides a general view of the present status of Industry 4.0 adoption by each GCC country. Therefore, it could serve as reference material for future studies that aim to develop the economic and market strength of the GCC region after taking into consideration the status of Industry 4.0 adoption by the logistics industries of these countries.